Avaliação do efeito da seleção para precocidade sexual em características de importância da raça nelore - Barbosa, Maria Mikaella Pacheco [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
A precocidade sexual em novilhas está relacionada com aumento na lucratividade do sistema de produção, principalmente por reduzir o ciclo de produção, promover maior viabilidade econômica ao sistema, aumentar a intensidade de seleção e maior ganho genético. Assim, objetiva-se: a) avaliar as principais diferenças entre novilhas Nelore com maior potencial v.s. menor potencial genético para precocidade sexual para características relacionada ao crescimento, desempenho produtivo e reprodutivo das fêmeas, e b) avaliar as relações genéticas para precocidade sexual e suas associações com características de importância econômica em bovinos da raça Nelore. O conjunto de dados incluiu informações fenotípicas de aproximadamente 300 mil novilhas Nelore e as características fenotípicas avaliadas forma relacionadas a eficiência reprodutiva: 1 - ocorrência de prenhez precoce aos 14 (PP14) 18 (PP18) e 24 (PP24) meses ; 2 – reconcepção (REC), 3 - número de progênies até os 53 meses de idade (NC53) e 4 - habilidade de permanência no rebanho (Stay) e para crescimento: 1 - peso a desmama (PD) e ao sobreano (PS); 2 – ganho de peso diário da desmama ao sobreano (GPD-S); 3 - peso a maturidade da fêmea (PM); 4 - peso ao desmame da primeira progênie (Pesodprog) e escores de avaliação visual para conformação (Conf), precocidade (Prec) e musculatura (Musc). A PP14 apresentou maior média para as características de crescimento (PD, PS e GPD-S) diferindo estatisticamente com PP18, PP24 e Tardia (PP > 24), e menor peso a idade adulta (PM) em comparação com PP24 e Tardia (PP > 24). Novilhas precoces (PP14 e PP18) apresentaram a primeira progênie cerca de 4% mais leve do que fêmeas tardias (PP > 24), embora apresentem uma maior NC53. Com relação à permanência, as novilhas precoces (PP14 e PP18) apresentaram 20% e 33% a mais de chances de permanecer no rebanho até 6 anos quando comparadas com novilhas tardias. Com relação ao efeito das classes de PS e GPD-S, os resultados sugerem que com o aumento do PS e GPD-S a probabilidade de novilhas engravidarem aos 14, 18 e 24 meses aumentam. No entanto, fêmeas PP14 e PP18 com peso maior que 326 apresentaram uma pequena redução na probabilidade de prenhez precoce. Correlações genéticas entre características de crescimento (PD, PS, GPD-S e PM) foram de fracas (rg = 0.10 ± 0.05; PS vs PP14) a moderadas (rg = -0.47 ± 0.07; PM vs PP14). As características NC53 e Stay apresentaram maiores estimativas de correlação genética com PP14 (rg = 0,53 e 0,45) e reduziu a medida em a idade aumento PP18 (rg = 0,46 e 0,38) e PP24 (rg = 0,35 e 0,39). A correlação genética entre prenhez precoce e escore visual para Conf, Prec e Musc foram fracas e favoráveis para a redução à idade ao primeiro parto. Portanto a prenhez precoce aos 14 meses em rebanhos de bovinos de corte criados apresenta benefícios nos sistemas de produção.

Sexual precocity in heifers is related to an increase in the profitability of the production system, mainly by reducing the production cycle, promoting greater economic viability to the system, increasing selection intensity, and greater genetic gain. Thus, the objective is: a) to evaluate the main differences between Nellore heifers with higher potential vs. the lower genetic potential for sexual precocity for traits related to growth, productive and reproductive performance of females, and b) to evaluate the genetic relationships for sexual precocity and its associations with traits of economic importance in Nellore cattle. The dataset included phenotypic information from approximately 300,000 Nellore heifers, and the phenotypic characteristics evaluated were related to reproductive efficiency: 1 - occurrence of early pregnancy at 14 (EP14), 18 (EP18), and 24 (EP24) months; 2 - heifer rebreeding (HR), 3 - number of progenies up to 53 months of age (NP53) and 4 - the ability to stay in the herd (Stay) and for growth: 1 - body weight at weaning (WW) and yearling (WY); 2 – average daily weight gain from weaning to yearling (ADGW-Y); 3 - weight at maturity of the female (WM); 4 - weight at weaning of the first progeny (WWprog) and visual scores for conformation (Conf), precocity (Prec) and musculature (Musc). To evaluate the effect of the WY and ADGW-Y class on EP14, EP18, and EP24, the WY and ADGW-Y characteristics were divided into 6 classes based on the quartile of their distribution, and generalized mixed models (GLM) were used, assuming a binomial distribution of the data with logit binding function. The differences between heifers classified as EP14, EP18, EP24, and late (EP > 24) were performed by contrasting the solutions of their effects in the mixed animal model for the characteristics of growth, productivity, and reproductive performance of the females. The genetic and phenotypic correlations between EP14, EP18, and EP24 with growth traits and productive and reproductive performance of females were estimated by Bayesian inference, using a bivariate mixed animal model. The EP14 showed a higher average for growth traits (WW, WY, and ADGW-Y) differing statistically with EP18, EP24, and Late (EP > 24), and lower weight at maturity (WM) compared to EP24 and Late (EP > 24). Early heifers (EP14 and EP18) presented the first progeny about 4% lighter than late heifers (EP > 24), although they present a higher NP53. Regarding permanence, early heifers (EP14 and EP18) were 20% and 33% more likely to remain in the herd for up to 6 years compared to late heifers. Regarding the effect of WY and ADGW-Y classes, the results suggest that with increasing WY and ADGW-Y, the probability of heifers becoming pregnant at 14-, 18-, and 24-months increases. However, EP14 and EP18 females weighing more than 326 showed a small reduction in the probability of early pregnancy. Genetic correlations between growth traits (WW, WY, ADGW-Y and PM) ranged from weak (rg = 0.10 ± 0.05; PS vs EP14) to moderate (rg = -0.47 ± 0.07; PM vs EP14). The NP53 and Stay traits showed higher estimates of genetic correlation with EP14 (rg = 0.53 and 0.45) and reduced the measure of increasing age EP18 (rg = 0.46 and 0.38) and EP24 (rg = 0.35 and 0.39). The genetic correlation between early pregnancy and visual scores for Conf, Prec, and Musc was weak and favorable for age reduction at first calving. Early pregnancy at 14 months in beef cattle herds shows benefits in production systems.
Evaluation of the effect of selection for sexual precocity on important traits of the nelore breed
Keywords: Bovinos de corte Pesos e medidas; Nascimento; Estimativa de parâmetros; Genética animal